HALYCH IN PHOTOS. THE FIRST KNOWN PHOTOS OF THE CITY OF 1885 - CHEMERYNSKYI, Andrii (Halych. Scientific work collection, 2020)
The article is devoted to the first known photograph of the city of Halych and its author. Unlike other cities in Galicia as part of the Austro-Hungarian monarchy, whose photographs are known earlier (Lviv, 1839; Stanislaviv, 1860), the first known photograph of Halytchyna dates back to 1885. General information about the photograph and biography of its author is given. The first photos of Halych are a valuable source of information about the appearance of the city and its individual objects at that time.